INTERNATIONAL STUDENTS' PERCEPTION OF TEACHING MICROBIOLOGY, VIROLOGY AND IMMUNOLOGY AT MEDICAL UNIVERSITIES IN UKRAINE - Valentyna Melnyk; Galyna Mikhnenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
The increase in the number of international students at medical universities in Ukraine has made great demands for the quality of instruction in the first three years of study when adaptation of these students takes place. The aim of the paper is to analyse international students' perceptions of teaching Microbiology, Virology and Immunology (MBVI) at Bogomolets National Medical University and outline the recommendations. A mixed research method was applied; the questionnaire with close-ended and open-ended questions grouped in nine sets was developed. Anonymous survey was conducted with the students (N=104) after completing the MBVI course with English as a medium of instruction. The survey has indicated general satisfaction of the respondents with the course. Insufficient proficiency in English often affects the quality of learning, and a low level of the Ukrainian or Russian language skills create difficulties in their communication and effective integration to the Ukrainian cultural environment. The survey results have shown the positive attitude of the respondents to the lectures with the requirement to have more interactive communication between the lecturer and students as well as have identified the difficulties concerning practical classes and self-study. The recommendations on how to improve academic performance of international medical students have been given. The focus is on increasing and maintaining language skills, consideration of ethnic and psychological features of students from different countries and implementing interactive teaching methods so that effective interaction in the learning environment could be achieved.